2011
DOI: 10.1186/1749-8090-6-70
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of lung vital capacity before and after coronary artery bypass grafting surgery: a comparison of incentive spirometer and ventilometry

Abstract: BackgroundMeasurement of vital capacity (VC) by spirometry is the most widely used technique for lung function evaluation, however, this form of assessment is costly and further investigation of other reliable methods at lower cost is necessary. Objective: To analyze the correlation between direct vital capacity measured with ventilometer and with incentive inspirometer in patients in pre and post cardiac surgery.MethodologyCross-sectional comparative study with patients undergoing cardiac surgery. Respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
(18 reference statements)
0
9
0
2
Order By: Relevance
“…Some studies 23 have tried to assess and / or correlate the SVC with other devices, however it was not found studies using the voice as a means of estimating the SVC.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies 23 have tried to assess and / or correlate the SVC with other devices, however it was not found studies using the voice as a means of estimating the SVC.…”
Section: Resultsmentioning
confidence: 99%
“…The attempt to evaluate the SVC by other methods different of spirometry has been described in the literature. Pinheiro et al 10 to justify the high cost of conventional techniques and the low availability of ventilometer and/or spirometers in clinical practice proposed as an alternative to this problem using an equipment used for incentive spirometry (IS) to be a cheaper and easier method. However, although the study have shown a higher correlation between the SVC and EI as compared with SVC and counting technique data found in this study (r = 0.95 vs r = 0.76 both with p <0.001 ), the use of EI differs from the main objective of this research did not use specific devices, in addition, the authors did not discuss the reason and not justified to have presented an equation for the evaluated variables that would possibly be used to estimate the SVC in their results.…”
Section: Discussionmentioning
confidence: 99%
“…As pulmonary function is directly associated with voice production, individuals with lung disease may have altered the MPT and reduction in the amount of air available to support phonation, characterizing a problem in controlling the airflow 3,8,9 . The use of specific devices for pulmonary evaluation, addition to have a high commercial value, is not always available in clinical practice 10 . Therefore, the use of an alternative technique may be useful for evaluating patients in private clinics, family health programs and hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals hospitalized can have decreased SVC regardless of the reason that led to hospitalization, and identify this functional limitation in various diseases, can help treat them adequate [3][4][5][16][17][18] . Vital capacity lower than 20 ml/kg is described in the literature 5 as an important value to trace possible interventions in patients regardless of the related disease, confirming the purpose of this research that does not separate individuals by disease, indicating that simply viewing a decrease in these values for starting treatment.…”
Section: Discussionmentioning
confidence: 99%